Children and adolescents with sickle cell disease have worse cold and mechanical hypersensitivity during acute painful events - Brandow, Amanda M. (Pain, 2019)
Sickle cell disease (SCD) pain associates with cold temperature and touch. Patients and murine models with SCD have baseline thermal and mechanical pain. In SCD mice, the baseline hypersensitivity is exacerbated by experimental vaso-occlusive crises. We hypothesized that SCD patients will similarly experience increased hypersensitivity to thermal and mechanical stimuli during acute painful events compared to baseline health. We conducted a prospective study of 24 SCD patients ages 7–19 yrs. Patients underwent quantitative sensory testing to thermal (cold/heat) and mechanical stimuli on the thenar eminence of the non-dominant hand (glabrous skin) and the lateral dorsum of the foot (hairy skin) during baseline health and within 48 hrs of hospitalization for acute pain. Primary outcomes were changes in: 1) Cold Pain Threshold (°C), 2) Heat Pain Threshold (°C) and 3) Mechanical Pain Threshold (g). Median age was 10.5 (IQR 9–14.8) yrs, 67% were female and 92% were on hydroxyurea. SCD patients had increased cold pain sensitivity in the hand during hospitalization compared to baseline [25.2°C (IQR 18.4–27.5°C) vs. 21.3°C (IQR 4.9–26.2°C); p=0.011] and increased mechanical pain sensitivity in the foot during hospitalization [0.32g (IQR 0.09–1.1g) vs. 1.7g (IQR 0.4–8.3g); p=0.003]. There were no differences in heat pain sensitivity. The increased cold (p=0.02) and mechanical (p=0.0016) pain sensitivity during hospitalization persisted after adjusting for age, gender, hydroxyurea use, opioid consumption and numeric pain score. Thus, cold and mechanical pain is significantly worse during an acute SCD painful event as compared to baseline health in patients with SCD.